Mental Wellbeing at Workplace: An Emerging Driver of Employee Performance and Organisational Success (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Mental health of workforce is a significant aspect of sustainable organisational performance. The study highlights the rising trend of mental health issues post pandemic that is creating an alarm for organisations to address the issue on urgent basis. The study tries to identify the critical factors affecting mental health of an employee. Inputs from published articles, research papers, global health surveys and organisational case studies shows that mental wellbeing reduces stress, anxiety, burnout, and absenteeism and promotes greater job satisfaction and organisational productivity. The study concludes that organisations should integrate mental health and wellbeing initiatives into strategic practices to build a resilient and productive workforce for greater competitive advantage.